Ensaios sobre estrutura a termo da curva de juros e spreads de títulos corporativos - Palaia, Daniel Rodolfo Antonelli (2014)
This work consists of three chapter dedicated to discussing different aspects of the important North American market for corporate bonds. In the first chapter, we show the evolution of the American credit market in recent decades, concerning its relevance to the economy. In this study we also show major regulatory changes that significantly affected the market in recent decades, as well as some references that indicate how these changes impacted the price and liquidity of credit assets. Finally, this chapter illustrates the main theoretical works and their contributions in the area of spreads and term structure of the corporate yield curve. In the second chapter, 'Global and Idiosyncratic Latent Factor in the Term Structure of Corporate Yield Curve Bonds', we analyze, in an unprecedented way, how global and idiosyncratic factors influence the term structure of the yield curves for corporate issuers from different ratings, activity sector and period of analysis. The results are unprecedented for this asset class because they had never been applied before to sovereign curves. The results indicate that the influence of global components decrease as the rating worsens. A second important result is that curves, for different sectors such as financial and industrial, are influenced differently by global and idiosyncratic factors regarding the level components and slope. In the third chapter, 'Term Structure of Corporate Bond Spreads Curve' we study the determinants of level and slope factors in corporate spreads in the United States from February 2002 to September 2012. The estimated model incorporates, unlike previous studies, latent factors of yield curves and treasuries spreads, macroeconomic and sectoral variables. We conclude that the level component of the treasury yield curve positively affects the level of spreads. The results differ from traditional literature, but are in line with recent studies that control periods of high assets volatility with structural breaks.